Challenges of the Industry 4.0: digital technologies in pharmaceutical industry - Ibrić, Svetlana (Archives of Pharmacy, 2022)
The fourth industrial revolution brought with it the development and application of advanced, digital technologies, in all segments of the pharmaceutical industry: from the discovery of new active substances to post-marketing monitoring of the drug. New, virtual technologies are: artificial intelligence, quantum computing, blockchain, telecommunications, Internet of Things, augmented, virtual and mixed reality. Many research and development centers in the pharmaceutical industry use artificial intelligence technologies in the discovery of new active substances, in silico modeling of drug release and absorption, optimization of drug formulation composition and production process and simulation of clinical trials. Blockchain technology is beginning to be used in drug distribution and makes it easier to reliably track pharmaceutical products at every step of the supply chain. In this way, the possibility of distributing counterfeit medicines can be reduced to a minimum. Virtual reality is used for drug discovery and design, enabling 3D visualization of drug molecular structures. In R&D laboratories, it is used in the planning of experiments; it can also be used in pharmaceutical education. In Mixed Reality, elements from the real and virtual worlds coexist, allowing users to "enter" the combined world of real and digital and move through it using state-of-the-art tools and sensors. There are a number of challenges that need to be overcome in order to accelerate the use of new and revolutionary virtual technologies, but the benefits of applying these technologies and the opportunities they provide in the advancement of the pharmaceutical industry are promising.